PERTUMBUHAN BIBIT KELAPA SAWIT DARI BERBAGAI UMUR YANG MENGALAMI CEKAMAN GENANGAN AIR YANG DIBERI BERBAGAI KONSENTRASI PUPUK PELENGKAP CAIR - Kristina, Masnur; Tabrani, Gunawan; ', Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to gain palm oil seed that fulfill quality standard while give liquid  complementary fertilizerthough the seeds that stressed by flooding. The research was done in a Completely Randomized Design 3x3 and 3 replication. The first factor is seeds age, there are u0 = 3 months, u1 = 5 months, and u2 = 7 months age of palm oil, and the second factor is concentrate of liquid  complementary fertilizer, there are p0 = 0 ppm, p1 = 6 ppm, and p2 = 12 ppm. Data were analyzed by analysis of variance andfurthertestedusingDuncan`sNewMultiple RangeTestatthe level of 5%,to decide criteria of seeds quality used standard of seeds quality according to Sihombing (2013). The result of research shows that there is no interaction between seeds age and concentrate of liquid  complementary fertilizer on all observation variable. Seeds which is 5 months old and have stressed by flooding fulfill standard of seeds quality, but seeds which is 3 months and 7 months old don’t fulfill the standard of seeds quality only on height diference seeds. The ratio of roots, dry weight of seeds, and standard index of palm oil seed that stressed by floodingare better if we give liquid  complementary fertilizer in 6 to 12 ppm. Key words : Palm oil seeds, flooding stress,liquid  complementary fertilizer, growth.